Nonsteroidal Anti-Inflammatory Drugs and Prostatic Diseases. (12th May 2014) - Ishiguro, Hitoshi; Kawahara, Takashi
Abstract : Prostatic diseases are characterized by increased activity of cytokines, growth factors, and cyclooxygenases- (COX-) 1 and 2. Activation of COX-1 and COX-2 results in increased levels of prostaglandins and the induction of angiogenic, antiapoptotic and inflammatory processes. Inhibition of COX enzymes by members of the widely used nonsteroidal anti-inflammatory drug (NSAID) class of drugs decreases prostaglandin production, and exerts a variety of anti-inflammatory, antipyretic, and antinociceptive effects. While numerous in vitro, in vivo, and clinical studies have shown that NSAIDs inhibit the risk and progression of prostatic diseases, the relationship between NSAIDs and such diseases remains controversial. Here we review the literature in this area, critically analyzing the benefits and caveats associated with the use of NSAIDs in the treatment of prostatic diseases.